Peran Orang Tua Dalam Pendidikan Anak: Analisis Undang-Undang tentang Perlindungan Anak dalam Perspektif Hukum Islam - Erfin, Zaitun; Irham, M. Iqbal (Nagari Law Review, 2023)
This study aims to explain parents' role in educating children by analyzing Law No. 20 of 2003 on the national education system and Law No. 35 of 2014 on child protection. This research employs a qualitative descriptive method and literature review. Data collection involves gathering information from various sources, such as books, magazines, and online news, followed by reading and recording the information. The research data is analyzed descriptively. The findings indicate that Law No. 20 of 2003 and Law No. 35 of 2014 can be divided into two parts: (1) fundamentals, functions, and objectives of the national education system; rights and obligations of citizens, parents, society, and government; learners; and types of education; (2) the role of parents in raising children includes nurturing, caring, educating, protecting, fostering the child's development according to their abilities, talents, and interests, preventing child marriage, imparting character education, and instilling moral values in children. In the context of fiqh siyasah, both Law No. 20 of 2003 and Law No. 35 of 2014 mandate parents to provide education to their children because education is the child's right, ensuring their well-being and guaranteeing fundamental rights stipulated in Islamic law.